Immunodominant antibody responses directed to SARS-CoV-2 hotspot mutation sites and risk of immune escape - Oliveira, Jamille Ramos; Ruiz, Cesar Manuel Remuzgo; Machado, Rafael Rahal Guaragna; Magawa, Jhosiene Yukari; Daher, Isabela Pazotti; Urbanski, Alysson Henrique; Schmitz, Gabriela Justamante Händel; Arcuri, Helen Andrade; Ferreira, Marcelo Alves; Sasahara, Greyce Luri; de Medeiros, Giuliana Xavier; Júnior, Roberto Carlos Vieira Silva; et al. (Frontiers in Immunology, 2023)
Considering the likely need for the development of novel effective vaccines adapted to emerging relevant CoV-2 variants, the increasing knowledge of epitope recognition profile among convalescents and afterwards vaccinated with identification of immunodominant regions may provide important information. Using an RBD peptide microarray to identify IgG and IgA binding regions in serum of 71 COVID-19 convalescents and 18 vaccinated, we found a set of immunodominant RBD antibody epitopes, each recognized by more than 30% of the tested cohort, that differ among the two different groups and are within conserved regions among betacoronavirus. Of those, only one peptide, P44 (S415-429), recognized by 68% of convalescents, presented IgG and IgA antibody reactivity that positively correlated with nAb titers, suggesting that this is a relevant RBD region and a potential target of IgG/IgA neutralizing activity. This peptide is localized within the area of contact with ACE-2 and harbors the mutation hotspot site K417 present in gamma (K417T), beta (K417N), and omicron (K417N) variants of concern. The epitope profile of vaccinated individuals differed from convalescents, with a more diverse repertoire of immunodominant peptides, recognized by more than 30% of the cohort. Noteworthy, immunodominant regions of recognition by vaccinated coincide with mutation sites at Omicron BA.1, an important variant emerging after massive vaccination. Together, our data show that immune pressure induced by dominant antibody responses may favor hotspot mutation sites and the selection of variants capable of evading humoral response.